Young Entrepreneurs in Sub-Saharan Africa - V. Gough, Katherine; Langevang, Thilde (Routledge spaces of childhood and youth series, 2017)
rs, Professor Ernest Aryeetey, Professor Craig Jeffrey, and Professor Peter Rosa, along with all the other participants, provided useful feedback and encouraged us to proceed with presenting the key project findings in book form. A string of people provided support for the project and the book along the way. At the host institution - the Department of Geography, University of Copenhagen - the untiring assistance of Dorthe Hallin with the accounts was invaluable, and in the closing stages Kent Pørksen kindly helped produce the maps at short notice. Wisdom Kalenga and Cecilia Gregersen both spent time at CBS providing assistance with the data analysis and conference support. Maheen Pracha did an excellent job editing the entire manuscript while Jo Woods assisted in the final checking and layout. Thanks are also due to Faye Leerink at Routledge for seeing the potential of the book and for agreeing to allow it to be subsequently published in sub-Saharan Africa, which we hope will ensure it is also widely read there. As all of the project participants spent lengthy periods of time in the field and/ or visiting other academic institutions, many families have had to cope with these absences. We thank them for their forbearance and for supporting the respective team members in their studies and travels. Hopefully they feel it was worthwhile in the end. While producing this book has been a major effort, it marks the end of an era that started back in November 2008 when we first started devising the project in response to a call from FFU for projects on youth employment. We are extremely grateful to all of the "YEMP family", as the project team came to be known, for their dedication to the project and for making it such a rewarding and fun experience, and look forward to future collaboration